New Approach in Fixed Resource Allocation and Target Setting Using Data Envelopment Analysis with Common Set of Weights - Marzieh Ghasemi; Mohammad Reza Mozaffari; Farhad Hosseinzadeh Lotfi; Mohsen Rostamy malkhalifeh; Mohammad Hasan Behzadi (Complexity)
One of the mathematical programming techniques is data envelopment analysis (DEA), which is used for evaluating the efficiency of a set of similar decision-making units (DMUs). Fixed resource allocation and target setting with the help of DEA is a subject that has gained much attention from researchers. A new model was proposed by determining a common set of weights (CSW). All DMUs were involved with the aim of achieving higher efficiency in every DMU after the procedure. The minimum resources and targets allocated to each DMU were commensurate to the efficiency of that DMU and the share of DMU in the input resources and the output productions. To examine the proposed method, other methods in the DEA literature were examined as well, and then, the efficiency of the method was demonstrated through a numerical example.